2013
DOI: 10.1190/geo2012-0495.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying uncertainties in attenuation estimation at methane-hydrate-bearing zones using sonic waveform logs

Abstract: Application of seismic attenuation estimation using sonic waveform data is limited because the estimation methods have not yet been fully developed. Although the median frequency shift method is considered to be effective and robust compared to the conventional spectral ratio method, we demonstrated that the median frequency shift methods strongly depend on reference data under lower signal-to-noise ratios. We modified an existing median frequency shift method not to depend on arbitrarily choosing a reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Suzuki and Matsushima () proposed a robust method, which does not depend on an arbitrary choice of the reference value. We used this method to estimate the attenuation from sonic waveforms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Suzuki and Matsushima () proposed a robust method, which does not depend on an arbitrary choice of the reference value. We used this method to estimate the attenuation from sonic waveforms.…”
Section: Methodsmentioning
confidence: 99%
“…The intrinsic attenuation indicated a success in oil and gas studies compared with other seismic attributes such as the velocity. Many studies showed that the intrinsic attenuation can be used as an indicator of hydrates and free gas existence, and it allows to obtain information the degree of cementation of gas hydrates (e.g., Guerin and Goldberg ; Matsushima ; Priest, Best, and Clayton ; Shyam and Minshull ; Suzuki and Matsushima ). The intrinsic attenuation can also be used to distinguish gas and condensate from oil and water (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early 1980s various methods have been developed and applied to determine sonic attenuation from full waveform acoustic logs (Cheng, Toksöz and Willis ; Goldberg, Kan and Castagna ; Dasios, Astin and McCann ; Dasios, McCann and Astin ; Parra, Xu and Hackert ; Qi, Müller and Pervukhina, ). The current view is that the statistical averaging (SA) method yields the most accurate attenuation estimates and is superior to the widely used spectral ratio (SR) method in the presence of noise (Suzuki and Matsushima ). The original SA method for estimating P‐wave attenuation has been developed for sonic logging data acquired in the Ocean Drilling Program (Frazer, Sun and Wilkens ).…”
Section: Introductionmentioning
confidence: 99%
“…Sun and Frazer () propose yet another method by applying a linear fit with common‐shot gather data to recover the reference attenuation value. Suzuki and Matsushima () modify the SA method so that it does not depend on an arbitrarily chosen reference depth.…”
Section: Introductionmentioning
confidence: 99%